Compton Scattering of Thermal Disk Radiation with Black Hole Disk Winds - Keigo Fukumura (The Astrophysical Journal)
Galactic black hole (BH) X-ray binaries (XRBs) are known to exhibit episodic outbursts, during which accretion and spectral mode distinctively transition between low/hard and high/soft state. X-ray observations during high/soft state occasionally reveal a pronounced presence of a powerful disk wind in these systems. However, it is unexplored to date how such winds may influence disk emission in that regime. In this work, we consider an observational implication by Compton scattering of thermal disk radiation due to accretion disk winds by performing multidimensional Monte Carlo simulations in the context of a stratified wind of large solid angle launched over a large radial extent of the disk. The Compton-scattered thermal disk spectrum is computed for a different wind property, i.e., wind density and its radial gradient. We find that the intrinsic disk radiation can be significantly down-scattered by winds of moderate-to-high density to the extent that the transmitted spectrum can substantially deviate from the conventional multicolor-disk emission in a tangible way. We thus claim that the conventional treatment of spectral hardening in the disk atmosphere may be insufficient to fully account for the observed disk continuum in the presence of strong wind scattering. It is suggested that the effect of scattering process (by f _w ) should be incorporated to accurately evaluate an intrinsic disk spectrum besides the conventional hardening (color correction) factor (by f _c ). We argue that BH spin measurements using thermal continuum-fitting in transient XRBs may well be mildly (if not significantly) altered by such spectral “contamination.”